AVAILABILITY, PREPARATION AND USES OF HERBAL PLANTS IN KALINGA, PHILIPPINES - Ammakiw, Christina L.; Odiem, Marymina P. (European Scientific Journal, ESJ, 2014)
The study determined the level of awareness of the residents on the availability of the herbal plants; and level of knowledge on the preparation and uses of the herbal plants. It used the descriptive method of research with the questionnaire as main data gathering tool. Used the 3 point scale, weighted mean, and Chi-square (x2) with 5% significant level as statistical treatment and analysis. The residents were very aware of the availability of the (6) six herbal plants namely: akapulko (Cassia, alata L), ampalaya (Momordica charantia), bawang (allium Sativum), bayabas Psidium guavida L, tsaang gubat Carmona retusa, and Yerba (hierba) Buena (Mentha cordifelia) ; very knowledgeable on the preparation of the selected herbal plants by decoction and compression but only knowledgeable on the preparation by infusion; not knowledgeable on the uses of akapulko to cure cough, and as mouthwash and purgative; not knowledgeable on the anti-pyretic effect of ampalaya ; knowledgeable the uses of bawang ; and not knowledgeable on the use of bayabas to prevent nose bleeding. No significant relationship on the level of awareness on the availability, and knowledge on the preparation and uses of the selected herbal plants with the profile of the respondents were determined except ethnic origin. Dissemination and information campaign on tsaang gubat and yerba Buena; conduct of trainings on the preparation of herbal plants by infusion; information on the use of akapulko to cure cough, and as mouthwash and purgative, ampalaya as an anti-pyretic, and bayabas to prevent nose bleeding; conduct of more parallel studies; and program on the production and dispersal of herbal plants were recommended.